Similar structures but different mechanisms: Prediction of FABPs-membrane interaction by electrostatic calculation - Zamarreño, Fernando (2012)
The role of fatty acid binding proteins as intracellular fatty acid transporters may require their direct interaction with membranes. In this way different mechanisms have been previously characterized through experimental studies suggesting different models for FABPs-membrane association, although the process in which the molecule adsorbs to the membrane remains to be elucidated. To estimate the importance of the electrostatic energy in the FABP-membrane interaction, we computationally modeled the interaction of different FABPs with both anionic and neutral membranes. Free Electrostatic Energy of Binding (dE), was computed using Finite Difference Poisson Boltzmann Equation (FDPB) method as implemented in APBS (Adaptive Poisson Boltzmann Solver). Based on the computational analysis, it is found that recruitment to membranes is facilitated by non-specific electrostatic interactions. Also energetic analysis can quantitatively differentiate among the mechanisms of membrane association proposed and determinate the most energetically favorable configuration for the membrane-associated states of different FABPs. This type of calculations could provide a starting point for further computational or experimental analysis.